(untitled) (Research, Society and Development, 2022)
Humanity is going through a technological movement never seen before, in which information and communication reach an essential level in people’s lives. Thus, there is a need for schools to keep up with the technological evolution and make the most of the benefits that it can provide. In this context, the present work has as its theme the use of Information and Communication Technologies (ICT’) in the teaching-learning environment of the Anatomy discipline, more specifically the use of computer simulation in distance education classes in Health courses. A literature review was carried out using the scientific platform Scielo, using the following keywords: "Computer Simulation", "Distance Learning" and "Anatomy Teaching". It was verified that the role of computer simulation in the study of the human body, in which it contributes with the increase of quality of the results obtained and the reduction of costs and difficulties involved, as well as the several advantages of observing parts with multiple levels and angulation and non-destructive virtual anatomy. It was possible to verify that the visualization of anatomical parts in more than one dimension helps to materialize abstract concepts, expanding the possibilities of understanding complex concepts of anatomy.